CHARACTER EDUCATION OF FOOD LOCAL CULTURE VALUES IN THE PEOPLE OF KAMPUNG ADAT CIRENDEU IN WEST JAVA THROUGH EXEMPLARY - Rohmatulloh, Rohmatulloh; Aan Hasanah, Aan Hasanah; Ruswandi, Uus (Jurnal Pendidikan Karakter, 2020)
Customary village is small group of people who still survive and consistently preserve the culture and belief of their ancestors. Local cultural values deserve to be promoted to the application of character education in school. The qualitative research understanding the life and local cultural values is carried out in the people of Kampung Adat Cirendeu in West Java. The local culture of the Kampung Adat Cirendeu people holds the principle of ngindung ka waktu and mibapa ka jaman which has the meaning of maintaining identity but still keeping abreast of the times. One of the local cultural values that still preserves until today is the culture of cassava-based food as a substitute for rice. This culture has been going on for a century and become an inspiration for the national food diversification program. One of the preservation efforts is through the example of their ancestors. Promotion and granting food culture values to the character education in schools involve various educational stakeholders (teachers, educators, governments, people, and customary peoples) that should give an example to the students. The most effective method is to form students with character and in the end they will be familiar with local food culture and does not depend on rice. Keywords: Character education, Kampung Adat Cirendeu, Exemplary. PENDIDIKAN KARAKTER NILAI-NILAI BUDAYA LOKAL MAKANAN DI MASYARAKAT KAMPUNG ADAT CIRENDEU JAWA BARAT MELALUI KETELADANAN Desa adat adalah sekelompok kecil orang yang masih bertahan dan secara konsisten melestarikan budaya dan kepercayaan nenek moyang mereka. Nilai-nilai budaya lokal layak dipromosikan untuk penerapan pendidikan karakter di sekolah. Penelitian kualitatif yang memahami kehidupan dan nilai-nilai budaya lokal ini dilakukan pada masyarakat Kampung Adat Cirendeu di Jawa Barat. Budaya lokal masyarakat Kampung Adat Cirendeu memegang prinsip ngindung ka waktu dan mibapa ka jaman yang memiliki makna mempertahankan identitas tetapi tetap mengikuti perkembangan zaman. Salah satu nilai budaya lokal yang masih dipertahankan hingga saat ini yaitu budaya makanan berbasis singkong sebagai pengganti beras. Budaya ini telah berlangsung selama satu abad dan menjadi inspirasi bagi program diversifikasi pangan nasional. Salah satu upaya pelestariannya yaitu melalui contoh dari nenek moyang mereka. Promosi dan pemberian nilai-nilai budaya makanan untuk pendidikan karakter di sekolah melibatkan berbagai pemangku kepentingan pendidikan (guru, pendidik, pemerintah, masyarakat, dan masyarakat adat) yang harus memberikan contoh kepada siswa. Metode yang paling efektif yaitu membentuk para siswa dengan karakter dan pada akhirnya mereka akan terbiasa dengan budaya makanan lokal dan tidak bergantung pada beras. Kata kunci: Pendidikan karakter, Kampung Adat Cirendeu, teladan.